Neutral Fractional Stochastic Differential Equations Driven by Rosenblatt Process (Journal of Partial Differential Equations, 2018)
In this paper, we are concerned with a class of neutral fractional stochastic partial differential equations driven by a Rosenblatt process. By the stochastic analysis technique, the properties of operator semigroup and combining the Banach fixed-point theorem, we prove the existence and uniqueness of the mild solutions to this kind of equations driven by Rosenblatt process. In the end, an example is given to demonstrate the theory of our work.
Keywords: Fractional neutral SDEs; Rosenblatt process; existence and uniqueness.